Systematic review of first-trimester ultrasound screening for detection of fetal structural anomalies and factors that affect screening performance - Karim, JN; Roberts, NW; Salomon, LJ; Papageorghiou, AT (Wiley, 2016)
Objectives To determine the sensitivity and specificity of first-trimester ultrasound for the detection of fetal abnormalities and to establish which factors might impact on screening performance. Methods A systematic review and meta-analysis of all relevant publications was performed to assess the diagnostic accuracy of two-dimensional transabdominal and transvaginal ultrasound in the detection of congenital fetal anomalies prior to 14 weeks’ gestation. The reference standard was detection of abnormalities at birth or postmortem. Factors that may impact on detection rates were evaluated, including population characteristics, gestational age, healthcare setting, ultrasound modality, use of an anatomical checklist for detection of first-trimester anomalies and type of malformation included in the study. In an effort to reduce the impact of study heterogeneity on the results of the meta-analysis, data from the studies were analyzed within subgroups of major anomalies vs all types of anomaly and low-risk/unselected populations vs high-risk populations. Results An electronic search (until 29 July 2015) identified 2225 relevant citations, from which a total of 30 studies, published between 1991 and 2014, were selected for inclusion. The pooled estimate for the detection of major abnormalities in low-risk or unselected populations (19 studies, 115 731 fetuses) was 46.10% (95% CI, 36.88–55.46%). The detection rate for all abnormalities in low-risk or unselected populations (14 studies, 97 976 fetuses) was 32.35% (95% CI, 22.45–43.12%), whereas in high-risk populations (six studies, 2841 fetuses) it was 61.18% (95% CI, 37.71–82.19%). Of the factors examined for their impact on detection rate, there was a statistically significant relationship (P<0.0001) between the use of a standardized anatomical protocol during first-trimester anomaly screening and its sensitivity for the detection of fetal anomalies in all subgroups. Conclusion Detection rates of first-trimester fetal anomalies ranged from 32% in low-risk groups to more than 60% in high-risk groups, demonstrating that first-trimester ultrasound has the potential to identify a large proportion of fetuses affected with structural anomalies. The use of a standardized anatomical protocol improves the sensitivity of first-trimester ultrasound screening for all anomalies and major anomalies in populations of varying risk. The development and introduction of international protocols with standard anatomical views should be undertaken in order to optimize first-trimester anomaly detection.